Prognostic determinants in patients with non traumatic intracerebral hemorrhage: a real life report. Issue 5 (3rd September 2021) - Masotti, Luca; Grifoni, Elisa; Migli, Lavinia; Dei, Alessandro; Spina, Rosario; Calamai, Italo; Guazzini, Giulia; Micheletti, Irene; Cosentino, Eleonora; Pinto, Gabriele; Vanni, Simone
ABSTRACT: Background and aim : Nontraumatic intracerebral hemorrhage (ICH) remains a devastating disease for high in-hospital and long-term mortality and residual neurological disability. The aim of our study was to analyze the prognostic factors in patients managed for ICH in the real-life clinical practice. Materials and Methods : We retrospectively analyzed clinical and neuro-radiological data of consecutive patients admitted to our Hospital for ICH along 1 year. In-hospital mortality and 90-day modified Rankin scale (mRS) ≥4 were the study outcomes. Moreover, we compared patients admitted in Intensive Care Unit (ICU) with patients admitted in Stroke Unit (SU). Results : Ninety-eight patients with mean age ± SD 78 ± 12 years were enrolled. In-hospital and 90-day mortality were 36.7% and 41.8%, respectively. Patients who died had a significantly higher percentage of ICH volume >30 mL, irregular shape, lobar location, intraventricular hemorrhage (IVH), midline shift, hydrocephalus, hematoma enlargement, Glasgow Coma Scale (GCS) ≤9 at hospital admission, early neurological worsening (ENW), higher Hemphill ICH score, and underwent oro-tracheal intubation more frequently compared with patients who survived. Patients admitted to ICU were younger and significantly more critical compared with those who were admitted to SU. In-hospital mortality in patients admitted to ICU was 52.6% compared with 25% in patients admitted to SU (p < 0.01). Median mRS score at hospital discharge was 4 (IQR 3–5) and at 90 days was 4 (IQR 3–4). ENW, hematoma enlargement, Hemphill ICH score ≥3 and midline shift >10 mm were found independent risk factors for in-hospital mortality, while age was found as independent risk factor for 90-day mRS ≥4). Conclusion : In real life, prognosis of ICH is associated with clinical and radiological determinants. In our study ENW, hematoma enlargement, Hemphill ICH score ≥3 and midline shift >10 mm were associated with short-term mortality risk, while age with 90-day mRS ≥4.